Neurocysticercosis: Current Perspectives on Diagnosis and Management - Butala, Caitlin; Brook, T. M.; Majekodunmi, Ayodele O.; Welburn, Susan Christina (Frontiers in Veterinary Science, 2021)
Porcine cysticercosis, human taeniasis, and (neuro)cysticercosis are endemic in many low- and middle-income countries (LMIC) where they present a significant health burden to affected communities. Neurocysticercosis (NCC) is one of the leading causes of human epilepsy in many hyperendemic regions in Latin America, Asia, and sub-Saharan Africa. The World Health Organization (WHO) reports an estimated 2.5–8.3 million cases of NCC annually with a disability-adjusted life year (DALY) burden of 2.8 million, but as for all neglected tropical diseases (NTDs), these values are likely to be underestimated. Diagnosis of NCC is complex and most accurately diagnosed using clinical neuroimaging that is unavailable in most hyperendemic regions in LMIC. On January 28, 2021, WHO will launch its road map for the NTDs' “Ending the neglect to attain the Sustainable Development Goals: a road map for neglected tropical diseases 2021–2030.” Taeniasis/cysticercosis is targeted for control success considered as steady increase in the number of countries with intensified control in hyperendemic areas [increasing from 2 (3%) in 2020 to 4 (6%) in 2023, to 9 (14%) by 2025, and to 17 (27%) by 2030]. Cross-cutting targets that include 100% access to at least basic water supply, sanitation, and hygiene in areas endemic for NTDs and 75% integrated treatment coverage for preventative chemotherapy will additionally impact on the taeniasis/cysticercosis/NCC complex. With no vaccine available for humans, prevention of infection depends on communication to the public of the life cycle of a complex zoonosis to promote behavior change, underpinned by practical control measures including treatment of human taeniasis and (neuro)cysticercosis with albendazole and praziquantel [widely used as part of the mass drug administration (MDA) deworming programs], surgery where appropriate, and effective vaccination and deworming for pigs supported by meat inspection. Here, we review recent advances in tools and implementation for Taenia solium taeniasis/(neuro)cysticercosis (TSTC) control and milestones on the onward path to elimination.